The Texts of Funerals and Vigilances – the Song-Dictation - Gál Adél; Гал Одел; Adel Gal (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
Abstract. The present paper examines a novel aspect of folk literacy within the ethnographical research, which is an important part of the culture. The main theme of the study is some manuscripts from Shalank, which were used at funerals. The manuscripts are in quadruplicate, and contain only funeral songs. Besides this, I would like to emphasize the importance of an old custom, the dictation. It is a religious custom, which was typical of the Reformed Church in Transcarpathia.

Az alábbi munka a néprajzi kutatás egyik új irányával, a népi írásbeliséggel foglalkozik, mely a kultúra igen fontos része. A tanulmány középpontjában néhány salánki kézirat áll. A Halottas alkalmakra készített és írott könyv jelenleg négy példányban található meg a településen, mindegyikük temetési énekeket tartalmaz. Emellett szeretném felhívni a figyelmet a református közösségekben egykor oly jellemző szokásra, az énekdiktálásra.

Резюме. Це дослідження присвячене одному з нових напрямів етнографії – народній писемності, яка є важливою частиною культури. У публікації проаналізовано кілька рукописів з села Шаланки. Книжка «Halottas alkalmakra készített és írott könyv» («Книга, написана для випадків поховань померлих») існує в селі в чотирьох екземплярах, містить пісні для похоронів. Також окрему увагу приділено на такий звичай реформатських громад, як диктування пісень (вокальний диктант).
Az énekdiktálás és annak szövegei temetések és virrasztások alkalmával
Диктування пісень та їх тексти на відспівуваннях (заупокійних молитвах) та похоронах
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008907
Keywords: manuscripts from Shalank; funeral songs; songdictation